Predicting intention to take protective measures during haze: The roles of efficacy, threat, media trust, and affective attitude - Lin, Trisha Tsui-Chuan (2016)
The annual Southeast Asian haze pollution raises public health concerns in this region. Based on a modified Extended Parallel Process Model, this study examines efficacy (self- and response efficacy) and perceived threat (susceptibility and severity) and incorporates new constructs of media trust and affective attitude. Results from a web survey of 410 undergraduate students in Singapore shows that response efficacy to seek haze-related information mediates the association between perceived self-efficacy and intention to take protective measures during haze. Moreover, self-efficacy is negatively associated with affective attitude (e.g., fear and worry) towards haze-related health problems. Next, perceived severity and perceived susceptibility are positively associated with response efficacy and affective attitude. Affective attitude toward haze is a stronger predictor than response efficacy for behavior intention. Finally, trust in new media is positively associated with young Singaporeans’ affective attitude, which positively affects their behavior intention to take protective measures.